Avaliação da atividade antimicobacteriana da lignana diidrocubebina extraída da Piper cubeba e de seus derivados semissintéticos - Laurentiz, R.s. (2015)
ABSTRACT The antimycobacterial activity of the dihydrocubebin (1), a dibenzylbutanedioiclignan obtained from ethanolic extract of Piper cubeba seeds, and its derivatives were examined in vitro against three different strains of Mycobacterium using amicrodilution method. Among the lignans evaluated, the 3 and 4 samples were the most active ones, displaying MIC values of 62.5 μg/mL against M. avium and M. tuberculosis, respectively. The derivatives 2-6, obtained for partial synthesis, had different substituents in the carbons 9 and 9’, fact thatalters the polarity, solubility and restricts the free rotations between the bonds C8-C8’ in relation to the starting material (1). The structural differences among these compounds provide important information about the antimycobacterial structure-activity relationship of the dibenzylbutanodioic skeleton, obtained from natural source, such as a possible target for the development of more powerful drugs against tuberculosis.